Chromophobe renal cell carcinoma with clear cell features; a case report with review of literature - Anjum Ara; Shagufta Shahin; Kafil Akhtar; Shahid A Siddiqui; Mohammad Saleem (Society of Diabetic Nephropathy Prevention, 2021)
Renal cell carcinoma (RCC) accounts for 3.0% of all malignant lesions of the human body. The World Health Organization (WHO) has classified renal malignant epithelial tumors as-clear cell, papillary, chromophobe and collecting duct RCCs and benign tumors as oncocytoma and angiomyolipoma. Chromophobe RCC is a distinct and rare variant of RCC. It shows equal preponderance in males and females and most commonly presents in the 6th decade of life. Because of overlapping clinical and microscopic features in different variants of RCC and considering the significant implications of the subtypes in the prognosis and treatment of these tumors, the histological classification of RCCs is extremely important. Here we report a case of a 56-year-old male, who presented with urinary complaints of hematuria, and was diagnosed as chromophobe RCC with clear cell features on histopathology and radiographic imaging.